DARKSEID AND THE FIRES OF APOKOLIPS - Fridolfs, Derek; Levins, Tim; DC Comics, Inc. (North Mankato, Minnesota : Stone Arch Books, a Capstone imprint, 2017)
Darkseid has kidnapped Jason Blood and plans to free the demon Etrigan who, because of Merlin's curse, shares Jason's body--and it is up to the members of the Justice League to confront the supervillain on the planet Apokolips and discover why he needs Etrigan.
At head of title: Justice League.
RL 2-3.
IL 2-6.
Age 8+
Keywords: Darkseid -- (Fictitious character) -- Juvenile fiction; Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Magic -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Superheroes -- Fiction; Supervillains -- Fiction; Magic -- Fiction; Blessing and cursing -- Fiction